Objectively assessed disease activity and drug persistence during ustekinumab treatment in a nationwide real-world Crohn's disease cohort - af Bjorkesten CG; Ilus T; Hallinen T; Soini E; Eberl A; Hakala K; Heikura M; Jussila A; Koskela R; Koskinen I; Moilanen V; Nielsen C; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objective
Long-term evidence on ustekinumab treatment response and persistence in patients with Crohn's disease in a real-world setting is scarce. We performed a retrospective nationwide chart review study of long-term clinical outcomes in Crohn's disease patients treated with ustekinumab.
Methods
The study was conducted in 17 Finnish hospitals and included adult Crohn's disease patients who received an initial intravenous dose of ustekinumab during 2017-2018. Disease activity data were collected at baseline, 16 weeks, and 1 year from health records.
Results
The study included 155 patients. The disease was stricturing or penetrating in 69 and 59% had prior Crohn's disease-related surgeries, and 97% had a treatment history of at least one biologic agent. Of 93 patients with >= 1 year of follow-up, 77 (83%) were still on ustekinumab at 1 year. In patients with data available, from baseline to the 1-year follow-up the simple endoscopic score for Crohn's disease (SES-CD) decreased from 10 to 3 (P = 0.033), C-reactive protein from 7 to 5 mg/L, (P < 0.001) and faecal calprotectin from 776 to 305 μg/g (P < 0.001).
Conclusions
Ustekinumab treatment in patients with highly refractory Crohn's disease resulted in high long-term treatment persistence and significantly reduced disease activity, assessed with objective markers for intestinal inflammatory activity.